Elucidation of Phytochemical Content of Cupressus macrocarpa Leaves: In Vitro and In Vivo Antibacterial Effect against Methicillin-Resistant Staphylococcus aureus Clinical Isolates - Nashwah G. M. Attallah; Walaa A. Negm; Engy Elekhnawy; Elshaymaa I. Elmongy; Najla Altwaijry; Hala El-Haroun; Thanaa A. El-Masry; Suzy A. El-Sherbeni (MDPI AG, 2021)
Methicillin-resistant Staphylococcus aureus (MRSA) is an important human pathogen that causes various infections. The increasing resistance of MRSA to different antibiotics is widely spreading; therefore, plant extracts may be novel therapeutic alternatives. The phytochemical profiling of Cupressus macrocarpa Hartw. ex Gordon leaves in vitro, and in vivo, antimicrobial potential of its extracts against MRSA clinical isolates were explored. A phytochemical tentative identification of 49 compounds was performed in the leaves using LC-ESI-MS/MS; in addition, isolation, and structure elucidation of hesperidin and eriocitrin were achieved for the first time. The diethyl ether extract (DEEL) exhibited the best antibacterial effect with MIC values ranging from 2 to 8 µg/mL, which significantly reduced the growth and efflux activity in 48.78% and 29.26% of isolates, respectively. qRT-PCR showed a significant down expression of norA and norB genes, which significantly affected the bacterial cell morphology and had a non-significant effect on membrane depolarization (using flow cytometry). In a rat model, four groups were wounded and treated with normal saline or DEEL, or infected with MRSA, or infected and treated with DEEL. The regeneration of the epidermis, maturation of granulation tissue, and reduction of inflammatory cell infiltration were observed after treatment with DEEL. Thus, C. macrocarpa leaves may be a promising source for new antimicrobials against MRSA.